O'Level Islamiyat Textbook for Paper 2 - "Ibn, Nishat Hammad" (Bookmark: Lahore, 2022)
Fully revised and updated content matching the Cambridge International IGCSE/O-Level Islamiyat syllabus (0493/2058). Endorsed by Cambridge International Examinations, the (Latest) edition of the IGCSE/O-Level Islamiyat (0493/2058) Coursebook comprehensively covers all the knowledge and skills students need for IGCSE/O-Level Islamiyat (0493/2058) Written by renowned experts Hammad Ibn Nishat in IGCSE/O-Level Islamiyat (0493/2058), the text is written in an accessible style with international learners in mind. Covers all Syllabus topics. Self-assessment questions allow learners to track their progression and exam-style questions help learners to prepare thoroughly for their examinations. Contemporary contexts and applications are discussed throughout, enhancing the relevance and interest for learners. The Coursebook is easy to navigate with color-coded sections to differentiate between IGCSE and O-level content. This Point is only for IGCSE & O-Level Books Includes diagrams for more clarity.
Keywords: Islamiat-Textbook